Human Adipose-Derived Stem Cells Labeled with Plasmonic Gold Nanostars for Cellular Tracking and Photothermal Cancer Cell Ablation. Issue 4 (April 2017) - Shammas, Ronnie L.; Fales, Andrew M.; Crawford, Bridget M.; Wisdom, Amy J.; Devi, Gayathri R.; Brown, David A.; Vo-Dinh, Tuan; Hollenbeck, Scott T.
Abstract : Background: Gold nanostars are unique nanoplatforms that can be imaged in real time and transform light energy into heat to ablate cells. Adipose-derived stem cells migrate toward tumor niches in response to chemokines. The ability of adipose-derived stem cells to migrate and integrate into tumors makes them ideal vehicles for the targeted delivery of cancer nanotherapeutics. Methods: To test the labeling efficiency of gold nanostars, undifferentiated adipose-derived stem cells were incubated with gold nanostars and a commercially available nanoparticle (Qtracker), then imaged using two-photon photoluminescence microscopy. The effects of gold nanostars on cell phenotype, proliferation, and viability were assessed with flow cytometry, 3-(4, 5-dimethylthiazolyl-2)-2, 5-diphenyltetrazolium bromide metabolic assay, and trypan blue, respectively. Trilineage differentiation of gold nanostar–labeled adipose-derived stem cells was induced with the appropriate media. Photothermolysis was performed on adipose-derived stem cells cultured alone or in co-culture with SKBR3 cancer cells. Results: Efficient uptake of gold nanostars occurred in adipose-derived stem cells, with persistence of the luminescent signal over 4 days. Labeling efficiency and signal quality were greater than with Qtracker. Gold nanostars did not affect cell phenotype, viability, or proliferation, and exhibited stronger luminescence than Qtracker throughout differentiation. Zones of complete ablation surrounding the gold nanostar–labeled adipose-derived stem cells were observed following photothermolysis in both monoculture and co-culture models. Conclusions: Gold nanostars effectively label adipose-derived stem cells without altering cell phenotype. Once labeled, photoactivation of gold nanostar–labeled adipose-derived stem cells ablates neighboring cancer cells, demonstrating the potential of adipose-derived stem cells as a vehicle for the delivery of site-specific cancer therapy. Abstract : Supplemental Digital Content is available in the text.